Information System Audit of Learning Management System Using COBIT 5 Army Staff and Command School - Erfin Erfiana; Erwin Teguh Arujisaputra; Purwadi Purwadi (CoreID Journal, 2026)
In today’s digital era, information technology has become an integral part of education, with Learning Management System (LMS) serving as a key innovation supporting online teaching and learning processes. The Army Staff and Command School (Seskoad) uses LMS to enhance the effectiveness and efficiency of its educational programs. However, no audit of the LMS information system has been conducted at Seskoad, potentially exposing the system to operational and security risks, such as non-compliance with regulations and vulnerability to cyber attacks. This study aims to audit the LMS using the COBIT 5 framework to evaluate the Maturity Level of IT governance and information system management. The methodology includes observation, interviews, questionnaires, and triangulation of data. The audit results indicate that the LMS Maturity Level is at Level 2 (Managed) across all seven evaluated sub-domains (APO9, DSS01, DSS04, DSS05, DSS06, MEA01, MEA02), with deficiencies in documentation, risk management, and security governance. Recommended improvements include developing SOPs, conducting user training, and performing regular security audits. With systematic implementation over five years, it is expected that Seskoad’s LMS can reach Level 4 (Quantitatively Managed), enhancing effectiveness and efficiency of education and training in the military environment.